Sleep behavior and training load in adolescent elite basketball players during COVID-19 pandemic development - Kullik, L.; Kellmann, M.; Puta, C.; Jakowski, S. (Chronobiology International, 2022)
The COVID-19 pandemic caused strong restrictions in organized sports. Specifically, adolescent athletes, whose daily routine is usually determined by school and practice schedules, experienced a sudden lifestyle change. The aim of this study was to examine sleep and training patterns of German elite adolescent basketball players (N = 115, 15.70 ± 1.22 years, female = 32.17%) during different phases of the 2021 lockdown. Sleep and training behavior were documented by a subjective monitoring over 10 days at three different lockdown phases in February, April, and June/July. A linear mixed model approach was conducted for the statistical analyses. Sleep duration and time in bed decreased between phase 1 (prohibition of organized sports) and phase 3 (normal training conditions), while sleep efficiency and quality increased. There was no change in training duration over time, but in training intensity, which peaked in the third phase. This study contains meaningful evidence to analyze the lockdown-related return to practice process. Athletes were able to maintain training duration with alternative protocols during pandemic conditions. Interestingly, athletes slept less under non-lockdown conditions, but reported a better sleep quality. It is recommended to consider athletes` individual preferences when planning training and recovery schedules.